INTEGRATED ACCOUNTING AND REPORTING: INSTITUTIONAL APPROACH - TATYANA Serebryakova (Учёт. Анализ. Аудит)
Integrated reporting and integrated accounting are the categories recently introduced by professional communities which call for scientific research and systematization. How are they related to the accounting (financial) reporting, accounting itself, what is their position within the information system of organizations? The article justifies the necessity of introducing into accounting science such categories as “integrated accounting” and “integrated reporting” and shows the extent of interrelation between accounting and reporting and the newly introduced categories. The article also compares the theoretical definitions of the categories of accounting and reporting with the principles of integrated reporting published by the International Integrated Reporting Council and criticallyevaluated the provisions of integrated reporting as professional community see it. Finally, the conclusion is drawn of insufficient objectivity in criticizing financial reporting for the lack of information provided. The author questions the objectivity of integrated reporting based on the principles developed by the International Integrated Reporting Council. At the same time the author proves that integrated reporting as a result of integrated accounting has the right to live, but in this case it won’t be able to fully comply with the international principles developed by the International Integrated Reporting Council.